PERLINDUNGAN HUKUM BAGI PIHAK KETIGA PEMBERI JAMINAN HAK TANGGUNGAN DALAM HAL DEBITUR WANPRESTASI - , Oktorina Sabatini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to assess and determine how legal protection for third party guarantor mortgage right in case the debtor defaults. In this case that is pledged as collateral security rights do not belong to the debtor but to the third party, in which borrowers are in default. This study is an empirical law juridical uses secondary data and primary data, how to collect data in the juridical empirical legal research is to examine the case that there is in reality are kemudiandilanjutkan with a guidance interview. Location of the research conducted in the city of Yogyakarta, Yogyakarta Special Region. Samples / research subjects in this study is that the respondents in this case the creditor Bank Danamon, the debtor and the third party and his sources are Notary and PPAT in the province of Yogyakarta Special Region. Analysis of data used in this research is descriptive qualitative, ie data obtained from the study are presented descriptively and qualitatively analyzed. Based on the research and discussion that has been done can be concluded that a third party or in this case the owner of the goods does not guarantee the legal protection of the bank because the third party does not have a direct legal relationship with the bank. Third party only has a direct legal relationship with the giver encumbrance (debtor), so that the third party only to get legal protection of the donor encumbrance (the debtor) in accordance with the agreement made with third parties. Keywords: legal protection, the Credit Agreement, Mortgage